2015
DOI: 10.3917/spub.151.0027
|View full text |Cite
|
Sign up to set email alerts
|

Vulnérabilité périnatale et soutien social en période postnatale : une revue de la littérature

Abstract: The transition to parenthood is an important step during which individuals may experience a state of vulnerability with numerous and interconnected dimensions. The variousforms of postnatal support therefore need to be harmonised in order to support parents. Research is needed on the harmonisation of the various support networks, which raises significant challenges, especially in terms of resources, funding, and information exchange, that must be documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 33 publications
(165 reference statements)
0
4
0
6
Order By: Relevance
“…All the interviewed women were continuously integrated into well-functioning family, neighborly or social networks, which usually provided sufficient support in various situations [ 18 , 19 ]. Nevertheless, the women reported that overall social acceptance of their life decisions and equal treatment in regard to pregnancy, childbirth and motherhood was missing.…”
Section: Resultsmentioning
confidence: 99%
“…All the interviewed women were continuously integrated into well-functioning family, neighborly or social networks, which usually provided sufficient support in various situations [ 18 , 19 ]. Nevertheless, the women reported that overall social acceptance of their life decisions and equal treatment in regard to pregnancy, childbirth and motherhood was missing.…”
Section: Resultsmentioning
confidence: 99%
“…The transition to parenthood is an important step during which individuals may experience a state of vulnerability with numerous and interconnected dimensions (Hamelin-Brabant et al, 2015). Although the literature considers family support as an essential component to strengthening positive outcomes for women during pregnancy and afterbirth, the various forms of support therefore need to be harmonised in order to support parents.…”
Section: Discussionmentioning
confidence: 99%
“…Literature from various nations suggests social support as an essential component for strengthening positive outcomes to families experiencing transitional life events, such as childbearing and child rearing (Habel, Feeley, Hayton, Bell, & Zelkowitz, 2015;Hamelin-Brabant et al, 2015;Mbekenga et al, 2010;Mbekenga et al, 2011;McLeish & Redshaw, 2015). The case is not very different in Jordan, with maternal health studies and policies often assuming family support to be of benefit to women during labour, birth and postpartum (Khresheh, 2009(Khresheh, , 2010Khresheh & Barclay, 2009;Oweis, Gharaibeh, Maaitah, Gharaibeh, & Obeisat, 2012;Shaban, Hatamleh, Khresheh, & Homer, 2011;Yehia, Callister, & Hamdan-Mansour, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the experience of parents show that trust and ability in care change every day in everyday routine and provision of care to the infant (18)(19)(20) .…”
Section: Discussionmentioning
confidence: 99%